Glucocorticoids affect bone mineral density and bone remodelling in OVX sheep: A pilot study - Diana Cabrera; Frances M. Wolber; Keren Dittmer; Chris Rogers; Anne Ridler; Danielle Aberdein; Tim Parkinson; Paul Chambers; Karl Fraser; Nicole C. Roy; Marlena Kruger (Bone Reports, 2018)
The aim of this study was to validate the combination of ovariectomy and glucocorticoid treatment in sheep as a large animal model for osteoporosis by measuring the concentration of specific biomarkers in the blood of the sheep and measuring bone loss over five months. Aged Merino ewes were randomly allocated into four groups: control, ovariectomy (OVX), and two OVX groups receiving glucocorticoids—one group once-monthly for five months (OVXG), and the other for two months followed by no treatment for three months (OVXG2). Parameters measured were biochemical markers of bone turnover, areal bone mineral density, volumetric bone mineral density, and total and trabecular bone parameters. Ovariectomy increased the concentrations of bone resorption marker C-terminal telopeptides of type 1 collagen (CTx-1) and bone turnover marker serum osteocalcin (OC) concentrations in the OVX group compared to control sheep. The combination of ovariectomy and glucocorticoid treatment increased the concentrations of CTx-1 and decreased serum OC concentrations in the OVXG group compared to OVXG2. Femur and lumbar spine bone density were lower in experimentally treated groups when compared with the control group. Total and trabecular vBMD in the proximal tibia were significantly lower in the treatment groups when compared with the control group. A significant negative correlation between femoral bone density and CTx-1 was found. The results of this study suggest that the combination of OVX and glucocorticoids induces bone loss in a short period of time in sheep. Keywords: Osteoporosis, Sheep, Ovariectomy, Glucocorticoids, Bone mineral density, Bone turnover markers